What is sociology for? Four answers in four bar jokes - Mateus, S. (Palestra De que nos serve a Sociologia?, 1ª Escola de Verão Internacional do IS-UP, 2022)
Reflexion on what is sociology for, supported in 4 ideas: change, method and protocol, plurality & interaction.